Saving Francesca - Marchetta, Melina, 1965- (New York : Alfred A. Knopf, 2006)
Sixteen-year-old Francesca could use her outspoken mother's help with the problems of being one of a handful of girls at a parochial school that has just turned co-ed, but her mother has suddenly become severely depressed.
Horn Book Starred.
School Library Journal starred.
Wilson's Senior High School.
Young Adult
Keywords: Catholic schools -- Fiction; Depression, Mental -- Fiction; Family life -- Australia -- Fiction; Schools -- Fiction; Sexism -- Fiction; Catholic schools -- Fiction; Depression (Psychology) -- Fiction; Family life -- Australia -- Fiction; School stories; Sexism -- Fiction; Australia -- Fiction; Sydney (N.S.W.) -- Fiction; Australia -- Fiction; Sydney (N.S.W.) -- Fiction